2018
DOI: 10.1007/s00586-018-5650-9
|View full text |Cite
|
Sign up to set email alerts
|

F-waves of peroneal and tibial nerves in the differential diagnosis and follow-up evaluation of L5 and S1 radiculopathies

Abstract: Comparisons of F-waves between the same nerve on both sides and between peroneal and tibial nerves in the same leg may clearly increase the validity of F-waves for evaluating a specific motor root lesion of L5 or S1. Furthermore, a quantitative comparison of F-waves may provide additional information on the severity of individual root lesions and their progression even in the early stages of disease. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, few studies involving the quantitative evaluation of LR by MUNIX have been reported. Recently published studies confirmed that MUNIX in the lower limbs can be recorded reliably from the abductor hallucis (AH), the extensor digitorum brevis (EDB) and the tibialis anterior (TA); these muscles are most commonly affected in LR because up to 80% of LR involve the L5 and/or S1 roots …”
Section: Introductionmentioning
confidence: 96%
“…However, few studies involving the quantitative evaluation of LR by MUNIX have been reported. Recently published studies confirmed that MUNIX in the lower limbs can be recorded reliably from the abductor hallucis (AH), the extensor digitorum brevis (EDB) and the tibialis anterior (TA); these muscles are most commonly affected in LR because up to 80% of LR involve the L5 and/or S1 roots …”
Section: Introductionmentioning
confidence: 96%
“…The inclusion criteria for patients with LDH includes [13,14] (1) low back discomfort with referral of pain or paresthesias into a single lower limb following an L4/L5/S1 distribution pattern; (2) lumbosacral magnetic resonance imaging (MRI) or computer tomography (CT) that demonstrated unilateral L4/L5/S1 nerve root compression by herniated disc at the L3/4, L4/L5 or L5/S1 level; (3) conventional electrophysiologic studies including normal sensory nerve conduction studies and a needle EMG revealing the presence of disease only on the involved side of abnormal spontaneous activity and/or changes in motor unit action potential in muscles that were innervated by the involved L4/L5/S1 root. (4) Surgical ndings of unilateral compressed herniated discs at the L4/L5/S1 root on the involved side. (5) Postoperative drain for 3 days.…”
Section: Subjectsmentioning
confidence: 99%
“…Lumbar disc herniation (LDH) is a degenerative pathology, and it was estimated that approximately 70-80% of the adult population will be affected by this disease during their lifetime [1,2]. Lumbosacral radiculopathy caused by LDH always carries a series of signs and symptoms and often leads to surgical intervention when conservative management fails [2][3][4]. Traditional open discectomy through unilateral interlaminar approach has obtained satisfactory results [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The first category contains the diseases that involve long distances of nerves, such as peripheral neuropathy due to diabetes [ 3 , 4 ] or multifocal motor neuropathy [ 5 ]. The second category contains the diseases involving the proximal part of the nerve pathway while the distal part is healthy, such as radiculopathies [ 6 ] and plexopathies [ 7 ].…”
Section: Introductionmentioning
confidence: 99%